PENGARUH PEMBIAYAAN MURABAHA, MUDHARABAH DAN MULTI JASA TERHADAP PENCAPAIAN PROFITALITAS DAN PENGENDALIAN NON PERFORMING LOAN PADA BANK PEMBIAYAAN SYARI’AH - Slamet Slamet; Peny Cahaya Azwari; Rika Lidyah (LPPM Institut Pendidikan Nusantara Global, 2023)
Islamic Finance Bank which is identical to the micro and small business sector that is not touched by commercial banks, both conventional and Islamic. This research was conducted to analyze the extent of the influence of Murabaha, Mudharobah and Multi Service Financing on Profitability and Non Performance Finance. Risert used is quantitative method, data in the form of numbers either extracted directly from the results of research or the results of processing qualitative data into quantitative data. Data collection techniques through documentation and analyzed through multiple regression tests, partial t tests, simultaneous f tests and r2 determination tests, then there are two variables that research uses, namely independent variables and dependent variables. The results obtained from the three products in BPR Syari'ah that have an influence on profitability are murabahah financing, and mulitijasa while mudharabah financing has no influence. While murabahah financing, mudharabah financing, multiservice financing on NPF has no effect, and the effect of NPF on profitability has no significant effect on profitability.